Chlorophyll contents of corn submitted to fertigation with swine and fish wastewater (Research, Society and Development, 2021)
Fertigation with wastewater is an excellent alternative from an agronomic and environmental point of view, for the supply of nitrogen for the cultivation of corn. The aim of this study was to evaluate the comparative effect between fertigation with fish and swine wastewater at different dilutions in the chlorophyll index of corn leaves. The experiment was conducted in plastic vases, arranged in the open, at the experimental station of the Instituto Federal Goiano - Campus Rio Verde - GO. The soil used was classified as dystrophic Red Latosol, Cerrado phase, with a clay texture. The experimental design used was in randomized blocks, analyzed in a 2 × 4 subdivided plot scheme, with three replications. The treatments consisted of two sources of waste water (fish and pig farming) diluted in four proportions of water supply, being: recommended dose of waste water + 0, 25, 50, 75% of its volume in water supply. Chlorophyll contents were evaluated at 30, 60 and 90 days after sowing, quantifying: chlorophyll a, chlorophyll b, total chlorophyll and the SPAD index. The source of swine wastewater provides the highest content of chlorophyll a, chlorophyll b, total chlorophyll and SPAD reading at the end of the corn cycle.